Campur kode Wawancara Ikonik, kasus “Mayat dalam Gentong” - Maharani, Nazwa Alaida; Darmawan*, Rasid Sidik; Salsabila, Annisa Naufal; Nurfaujiah, Alya; Jannah, Nabila Izatul; Widyastuti, Temmy; Awaliah, Yatun Romdonah (Universitas Suryakanca, 2025)
The research is motivated by the phenomenon of code mixing in the iconic interview compilation, the case of